Caustic ingestion injuries: evaluation of 108 cases - Ali Önder KARAOĞLU; Ömer ÖZÜTEMİZ; Tankut İLTER; Yücel BATUR; Nadir YÖNETÇİ; Oktay TEKEŞİN; Ahmet MUSLUOĞLU; Ahmet AYDIN; Necla OSMANOĞLU; Ulus AKARCA; Hanefi ÇAVUŞOĞLU (Turkish Journal of Gastroenterology, 2019)
-